Hubungan Antara Kebersyukuran Dengan Subjective Well-Being Pada Guru Honorer Di Kabupaten Pringsewu - Saputri, Hindin (Program Studi Psikologi Islam, 2025)
Subjective well-being, or SWB, is an assessment or appraisal of life in which people report feeling satisfied with their lot in life, experiencing few negative feelings, and experiencing a lot of happy emotions. Gratitude is one element that may have an impact on SWB. The research objective was to determine the correlation between gratitude and the subjective well-being of honorary teachers in Pringsewu Regency. This research used a quantitative approach with a sampling technique, namely cluster random sampling. The subjects in this research were 267 honorary teachers in Pringsewu Regency. The analysis technique used is Spearman Rho analysis using SPSS 22 for Windows, which showed a correlation coefficient of 0.718 with a significant value of p = 0.000 (p < 0.01), meaning a significant positive correlation exists between gratitude and SWB. Gratitude has an effective contribution of 69.3% to SWB.